The need for eco-driving technologies in urban public transport - Ivan Slatov; Igor Murovanyi (Transport Technologies, 2023)
This article discusses the challenges facing public transport in Ukraine in terms of reducing fuel consumption and emissions. The absence or insufficient development of means and methods for monitoring driver behaviour, as well as high staff turnover, create significant difficulties in controlling drivers and vehicles. A conducted study in Lutsk, the administrative center of the Volyn region, analyzed the driving behavior of passenger buses in the city. Results showed that typical driving modes include idling (40%), acceleration (18%), driving at a constant speed (29%), and braking (13%). The study also revealed average accelerations and decelerations, and these results do not meet the requirements of ecological driving. The correlation between driver behavior and these dynamic acceleration and braking characteristics has been established. Possible causes for this phenomenon are discussed in the study. The article proposes the introduction of modern solutions to solve these problems. These solutions are Eco-Driving Assistance Systems (EDAS) or integrated systems, such as FleetControl from TRIONA, which can help learning operating conditions and reduce fuel consumption and emissions. These programmes can also serve as effective monitoring tools for individual drivers and transport companies. This paper describes these applications and reviews the research related to their use and development. In addition, the article highlights the importance of training drivers in eco-driving as a cost-effective method of improving fuel efficiency in transport companies. The paper concludes by emphasising the need for further research to fully understand the complexities of public transport in Ukraine and the potential benefits of introducing innovative technologies for a more sustainable and efficient future for the industry.